Analisis Posisi Bersaing dan Penentuan Strategi Bauran Pemasaran untuk Meningkatkan Nilai Penjualan pada Budhi Ayu Silver di Celuk Sukawati Gianyar - Ade Ruly Sumartini; I Gede Putra Ariwiguna (Warmadewa Management and Business Journal (WMBJ), 2019)
Budhi Ayu Silver Celuk Sukawati Gianyar implemented a marketing mix strategy consisting of activities aimed at product planning, pricing, distribution, promotion, people involved in marketing activities. The purpose of this study is to analyse competitive positions based on the Boston Consulting Group matrix, strengths, weaknesses, opportunities, threats and relevant marketing mix strategies to increase the sales value of Budhi Ayu Silver Company in Celuk, Sukwati. The analysis technique used in this study is the Boston Consulting Group and SWOT analysis. Based on the Boston Consulting Group analysis, it can be seen that the business position of Budhi Ayu Silver Celuk Sukawati Gianyar is in the cash cows with average market growth of 1.47% and relative market share of 1.01X. The results of the SWOT analysis are seen from internal variables that show the strength of the company, with a weighted value of 2.90. As for the power of Budhi Ayu Silver, it lies in the indicators of product type, product development, the price offered, a location of the company, service to consumers and arrangement of store space, as well as weaknesses in indicators of distribution channels, promotional activities and consumer facilities. Judging from the external variables with a weighted value of 2.43 indicators, the opportunity lies in the indicators of the development of tourist visits, Balinese culture, technological developments and security of Bali while the threats that Budhi Ayu Silver has to include signs of economic conditions, competing companies and political stability. Strategies that should be implemented Budhi Ayu Silver is a diversified strategy that is oriented towards utilising the power that is owned to be able to take advantage of the opportunities that exist. Budhi Ayu Silver Celuk Sukawati Gianyar melaksanakan strategi bauran pemasaran yang terdiri dari kegiatan yang ditujukan untuk merencanakan produk, harga, distribusi, promosi, orang-orang yang terlibat dalam aktifitas pemasaran. Adapun tujuan dari penelitian ini adalah menganalisis posisi bersaing berdasarkan matrik Boston Consulting Group, kekuatan (strenght), kelemahan (weakness), peluang (oppurtunity), tantangan (threats) dan strategi bauran pemasaran yang relevan untuk meningkatkan nilai penjualan pada Perusahaan Budhi Ayu Silver di Celuk, Sukwati. Teknik analisis yang dipergunakan dalam penelitian ini adalah Boston Consulting Group dan analisis SWOT. Berdasarkan analisis Boston Consulting Group maka dapat dilihat bahwa posisi bisnis pada Budhi Ayu Silver Celuk Sukawati Gianyar berada pada kuadran sapi perah (Cash Cows) dengan rata-rata pertumbuhan pasar sebesar 1,47% dan pangsa pasar relatif yaitu sebesar 1,01X. Hasil dari analisis SWOT dilihat dari variabel internal yang menunjukan kekuatan perusahaan, dengan nilai tertimbang sebesar 2,90. Adapun yang menjadi kekuatan Budhi Ayu Silver adalah terletak pada indikator jenis produk, pengembangan produk, harga yang ditawarkan, lokasi perusahaan, pelayanan kepada konsumen dan penataan ruangan toko, serta kelemahannya pada indikator saluran distribusi, kegiatan promosi dan fasilitas konsumen. Dilihat dari variabel ekternalnya dengan nilai tertimbang 2,43 indikator yang menjadi peluang terletak pada indikator perkembangan kunjungan wisatawan, kebudayaan Bali, perkembangan teknologi serta keamanan Bali sedangkan ancaman yang dimiliki Budhi Ayu Silver meliputi indikator kondisi perekonomian, perusahaan pesaing dan stabilitas politik. Strategi yang sebaiknya diterapkan Budhi Ayu Silver adalah strategi diversifikasi yang berorientasi pada memanfaatkan kekuatan yang dimiliki untuk dapat memanfaatkan peluang yang ada.